THE EFFECT OF CIRCUIT TRAINING AND INTERVAL TRAINING ON LEG MUSCLE ENDURANCE ON WOMEN'S VOLLEYBALL ATHLETES AT VELOCITA - Irfan, Irfan; Yasriuddin, Yasriuddin; Hudain, Muh Adnan; Martono, Martono (JURNAL PENDIDIKAN GLASSER, 2023)
This experimental research that aims to examine whether there is an influence of circuit training and interval training on leg muscle endurance of Velocita volleyball women athletes in Banggai regency. This is motivated by the low achievement of women’s volleyball in the Banggai regency which is due to a lack of ability to maintain the quality of the game due to low leg muscle endurance. The population is all Velocita women's volleyball athletes in Banggai district, totaling 12 people, while the sample uses the total sampling method so that the total is 12 athletes. The research data were obtained by giving a leg muscle endurance test in the form of squat jump test through the pretest and posttest after the athlete was given the training treatment. Data analysis techniques using t-test analysis. Based on the results of the analysis, it is discovered that (1) there is an influence of circuit training on leg muscle endurance of Velocita volleyball women athletes in Banggai regency with a tcount of 12,593 > 2,571 ttable and a p value of Sig. 0.000 is smaller than 0.05, (2) there is an influence of interval training on leg muscle endurance of Velocita volleyball women athletes in Banggai regency with a tcount of 7,906 > 2,571 ttable and a p value of Sig. 0.001 is smaller than 0.05, and (3) there is no difference in the influence of circuit training and interval training on leg muscle endurance of Velocita volleyball women athletes in Banggai regency where the results of the t test show tcount 1.958 smaller than ttable value 2.228 with a significance value of 0.079 greater than the value of α 0.05. It can be concluded that there is an influence circuit training and interval training on leg muscle endurance in Velocita women's volleyball athletes Banggai Regency significantly.